Where the Rubber Meets the Road: Examining Efficiency and Equity in Designing Summer Youth Employment Programs - Alicia Sasser Modestino; Mindy Marks; Hanna Hoover; Hitanshu Pandit (Institute of Labor Economics (IZA), 2025)
Summer Youth Employment Programs are known to have significant impacts on youth outcomes based on lotteries from oversubscribed programs. But most cities cannot use a lottery design due to heterogeneity across youth and jobs. How can programs achieve efficiency and equity under alternative assignment mechanisms? Using hiring platform data, we study youth application and employer selection behavior to explore these design challenges. We find large mismatches between the distribution of youth versus jobs leaving 10% to 25% of positions unfilled. Moreover, employers were nearly twice as likely to select white youth relative to their representation in the applicant pool. This disparity persisted when controlling for other demographics, the number and timing of applications, and job readiness. Our findings reveal that workforce development programs may perpetuate inequities in the absence of simple random assignment. Using a job matching algorithm, we show that placing just 30% of positions by lottery can improve both equity and efficiency.
Keywords: D63; D91; I38; J13; M51; 330; youth; workforce development; summer jobs; job matching; algorithm